PENINGKATAN IMPULSIVE BUYING EVENT HARBOLNAS SHOPEE MELALUI FoMO DAN HEDONIC SHOPPING - Dedi Andriansah (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2023)
The study aims to analyze the influence of Fear of Missing Out (FoMO) and Hedonic Shopping on impulsive buying decisions on Shopee’s e-commerce platform during National Online Shopping Day. (Harbolnas). Survey data is collected from students at the University of Logistics and International Business as a case study. Through data analysis using the Structural Equation Modeling (SEM) method, the study explored Fear of Missing Out (FoMO) and Hedonic Shopping during Harbolnas, as well as their impact on impulsive buying behavior. The types of data used in this study are primary data and secondary data. The population in the study amounted to 2,711 people, with a sample total of 350, the sampling technique used was non-probability purposive sampling. The results of the research showed that there was a positive and significant influence between Fear of Missing Out (FoMO) and impulsive buying during Harbolnas. In addition, it is proven that Hedonic Shopping also has a positive and significant influence on impulsive buying during Harbolnas. Implications of this study show that there is a significant influence between Fear of Missing Out (FoMO) and Hedonic Shopping on impulsive buying decisions on Shopee e-commerce platform during National Online Shopping Day. (Harbolnas).